PENGEMBANGAN QUIET BOOK SEBAGAI MEDIA PENGENALAN UNTUK PENCEGAHAN COVID-19 PADA ANAK USIA DINI - Rosa Handayani; Taat Kurnita Yeniningsih; Siti Naila Fauzia (Jurnal Ilmiah Mahasiswa Pendidikan Anak Usia Dini, 2021)
Keywords: Media, Quiet Book, Introduction to Covid-19 PreventionThe use of media in an introduction to the prevention of Covid-19 in early childhood is an important element to do. This is because with the presence of the media, introductory efforts to prevent Covid-19 will be more interesting and easier for children to understand. However, currently the availability of media in the introduction to the prevention of Covid-19 is not yet in accordance with the stages of the child's age. This research is a type of development research (Research and Development) which aims to produce a valid Quiet Book as an introduction medium for the prevention of Covid-19 in early childhood. Data collection in this study was carried out through observation, literature study and validation questionnaire sheets from media experts and material experts. The development of the initial concept in this study consisted of defining, designing, and developing stages. At the development stage, a validation test was carried out by a media expert with a score of 96% (very valid) and a score of assessment by a material expert of 96% (very valid). Then after a revision of the Quiet Book as an introduction media for the prevention of Covid-19, the percentage of the assessment score from media experts was 100% (very valid). And the percentage of the validation score from material experts is 100% (very valid). Thus, based on the results of validation from media experts and material experts, it can be concluded that the Quiet Book product as an introduction medium for the prevention of Covid-19 in early childhood is very valid as a medium for early childhood in the introduction to prevention of Covid-19.Abstrak, Penggunaan suatu media dalam pengenalan untuk pencegahan Covid-19 pada anak usia dini merupakan unsur penting untuk dilakukan. Hal ini dikarenakan dengan adanya media, upaya pengenalan untuk pencegahan Covid-19 akan menjadi lebih menarik dan mudah dipahami oleh anak. Namun saat ini ketersediaan media dalam pengenalan untuk pencegahan Covid-19 belum sesuai dengan tahapan usia anak.  Penelitian ini merupakan jenis penelitian pengembangan  (Research and Development) yang bertujuan untuk menghasilkan Quiet Book sebagai media pengenalan utnuk pencegahan Covid-19 pada anak usia dini yang valid. Pengumpulan data dalam penelitian ini dilakukan melalui observasi, studi literatur dan lembar angket validasi dari ahli media dan ahli materi. Pengembangan konsep awal pada penelitian ini terdiri dari tahap pendefinisian, perancangan, dan pengembangan. Pada tahap pengembangan dilakukan uji validasi oleh ahli media dengan pemerolehan skor sebesar 96% (sangat valid) dan skor penilaian oleh ahli materi sebesar 96% (sangat valid). Kemudian setelah dilakukannya revisi terhadap Quiet Book sebagai media pengenalan untuk pencegahan Covid-19, diperoleh persentase skor penilaian dari ahli media sebesar 100 % (sangat valid). Dan persentase skor validasi dari ahli materi sebesar 100 % (sangat valid). Dengan demikian, berdasarkan hasil validasi dari ahli media dan ahli materi dapat disimpulkan bahwa produk  Quiet Book sebagai media pengenalan untuk pencegahan Covid-19 pada anak usia dini sangat valid  sebagai media bagi anak usia dini dalam pengenalan untuk pencegahan Covid-19.Kata Kunci: Media, Quiet Book, Pengenalan untuk Pencegahan Covid-19